Demographic and Epidemiologic Profile of Tumours in Children in A Tertiary Paediatric Surgery Centre in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2020)
Background : The real demographic and epidemiologic profile of cancer in paediatric age group in Bangladesh is not known. The aim of this study is to provide a comprehensive recent knowledge of paediatric cancer in Bangladesh.  Materials and methods: We retrospectively reviewed records of all tumours admitted in the Department of Paediatric Surgery, Chittagong Medical College Hospital from January 2009 to December 2019 (11 years). Data were collected with regards to type of tumour, age, sex, frequency and age group specific distribution.  Results: There was a total of 131 patients. Male to female ratio was 1.29:1. Age ranged from 27 days to 14 years (Median 4 years).  75 patients were in 0-4 years, 38 in 5-9 years and 18 in 10-14 years age group. Nephroblastoma was the commonest tumour (32) followed by Neuroblastoma (16) and Sacrococcygeal teratoma (11).  Conclusion: There was a wide variation of tumour occurrence among age groups and between sexes. Cancer registry is needed for proper data recording of the casesJCMCTA 2020 ; 31 (2) : 43-48